Histories of technology, the environment, and modern Britain - Agar, Jon; Ward, Jake (UCL Press, 2018)
Histories of Technology, the Environment and Modern Britain brings together historians with a wide range of interests to take a uniquely wide-lens view of how technology and the environment have been intimately and irreversibly entangled in Britain over the last 300 years. It combines, for the first time, two perspectives with much to say about Britain since the industrial revolution: the history of technology and environmental history. Technologies are modified environments, just as nature is to varying extents engineered. Furthermore, technologies and our living and non-living environment are both predominant material forms of organisation - and self-organisation - that surround and make us. Both have changed over time, in intersecting ways. Technologies discussed in the collection include bulldozers, submarine cables, automobiles, flood barriers, medical devices, museum displays and biotechnologies. Environments investigated include bogs, cities, farms, places of natural beauty and pollution, land and sea. The book explores this diversity but also offers an integrated framework for understanding these intersections.